A Review of Jinayah Fiqh on the Phenomenon of Doxing and Character Assassination in the Media - Purnama Wahyuni; Mhd Irsan Akbar (AT-TAFAHUM: Journal of Law, 2023)
The era of digital disruption has shifted criminal patterns from physical space to cyberspace, where personal data is often used as a weapon for digital persecution. The phenomena of doxing (the unauthorized dissemination of personal identity information) and character assassination on social media are not merely violations of communication ethics, but rather systematic threats to the existence of human dignity (al-'irdh). This study aims to dissect these phenomena through the lens of Islamic Jurisprudence (Fiqh Jinayah) in order to formulate an appropriate legal construction for contemporary cybercrime. Using a qualitative descriptive-analytical research method and a normative-juridical approach, this article explores how Islamic law responds to actions that damage an individual's privacy and reputation. The results show that doxing and character assassination fulfill the elements of jarimah (criminal acts) because they contain elements of tajassus (espionage), backbiting, and slander, which are explicitly prohibited in the Qur'an and Sunnah. In the Islamic Jurisprudence (Fiqh Jinayah) classification, this act is categorized as Ta'zir Crime, where the state authority (Waliyyul Amri) has full authority to impose deterrent sanctions, ranging from fines (gharamah) to imprisonment, in order to uphold the main objective of sharia (Maqashid Syariah), namely the protection of honor. This article also emphasizes the importance of reintegrating Islamic moral values into cyber law regulations to reduce the number of "social deaths" for victims in the digital space.